The Effect of Different Plasticizers on the Characteristics of Whey Composite Edible Film - Fahrullah Fahrullah; Lilik Eka Radiati; Purwadi Purwadi; Djalal Rosyidi (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2020)
The edible film is a protective coating that could be directly applied to food products. This research aims to observe the physical characteristics of whey composite edible film with different plasticizer addition (glycerol, sorbitol, polyethylene glycol). The research was conducted as a laboratory experiment and the observed variables were film thickness, tensile strength, elongation at break, water vapor transmission rate (WVTR), and followed with microstructure observation. The research was conducted in a completely randomized design and analyzed with analysis of variance (ANOVA) followed with the least significant difference (LSD) test. The physical measurement of the edible film showed that the thickness was at 0.0286-0.0308 mm, the tensile strength was at 5.72-8.20 N, the elongation at break was around 28.66-57.5%, and the WVTR was at 7.63-7.96 g/m2.day. Moreover, the microstructure observation showed that the molecules in the edible film were evenly distributed.